Cytotoxicity of the Defensive Secretion from the Medicinal Insect Blaps rynchopetera - Xiao, Huai; Dong, Jian-Wei; Zhou, Di-Jiao; Wu, Xiu-Mei; Luo, Jian-Rong; Zhang, Cheng-Gui; Guo, Na-Na; Li, Yue; Cai, Le; Ding, Zhong-Tao (Molecules (Basel, Switzerland), 2017)
Blaps rynchopetera Fairmaire has long been used as a folk medicine by the Yi and Bai ethnic groups in China to treat fever, cough, gastritis, boils, and tumors. In the present study, the cytotoxicity of the defensive secretion (TDS) of B. rynchopetera against AGS Caco-2, HepG2 U251 and Bel-7402 was tested, and the results revealed that TDS had potent cytotoxicity against testing cells with IC50 values of 45.8, 17.4, 53.6, 98.4 and 23.4 μg/mL, respectively. Gas chromatography-mass spectrometry (GC-MS) analysis was employed to clarify the cytotoxic constituents in TDS of B. rynchopetera and five volatile compounds, including 2-ethyl-2,5-cyclohexadiene-1,4-dione (3, 31.00%), 1-tridecene (5, 28.02%), 2-methyl-2,5-cyclohexadiene-1,4-dione (2, 22.86%), hydroquinone (4, 1.33%), and p-benzoquinone (1, 1.01%), were identified. Chemical constituent investigation on TDS further supported the presence of 5 above compounds. A cytotoxic assay indicated that compounds 1, 2, 3 and 4 exhibited significant cytotoxicity against the testing cell lines, implying that benzoquinones and hydroquinone played important roles in the cytotoxicity of TDS of B. rynchopetera. TDS is a cytotoxic natural material and further studies investigating mechanisms and inhibitory activities on other cell lines is warranted.